ذوي الاحتياجات الخاصة ورعايتهم: نظرة قرآنية - Shumsudin Yabi; Amran Abdul Halim; Syed Najihuddin Syed Hassan; Aminuddin Basir; Fadlan Bin Mohd Othman; Akila Mamat (Centre of Quranic Research (CQR), University of Malaya, 2024)
Indexed by MyCite